Pengaruh Bimbingan Guru Pendidikan Agama Kristen Terhadap Moral Siswa Kelas X SMK Negeri 1 Palipi Tahun Pembelajaran 2022/2023 - Brigita Indah Sari; Wilson Simanjuntak; Nisma Simorangkir (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The aim of this research is to determine the positive and significant influence of Christian Religious Education teacher guidance on the morale of class X students at SMK Negeri 1 Palipi for the 2022/2023 academic year. The research method used is a quantitative research method. The population is all 122 class Data was collected using a positive closed questionnaire with 55 items, namely 22 items for variable /2023: 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.587 > rtable(=0.05,n=40) = 0.312. b) Testing a significant relationship obtained tcount= 4.474 > ttable(=0.05, dk=n-2=38)= 2.021. 2) Influence test: a) Regression equation test, obtained regression equation. b) Regression coefficient of determination test (r2) = 34.5%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=21, dk denominator=n-2=40-2=38) namely 19.98 > 1.51. Thus, Ha, namely that there is a positive and significant influence of Christian Religious Education teacher guidance on the morale of class